Kesetaraan Gender Dalam Pendidikan Islam Perspektif Muhammad Sa’id Ramadhan Al-Buthi - Sholihah, Aminatus; Mahfud, Muhammad; Ariffudin, Muhammad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this study is to describe gender equality in the field of education proposed by Muhammad Sa'id Ramadhan Al-Buthi. The qualitative research method is a literature study that is primarily sourced from the book Aisyah Ummul Mu'minin Ayyamuha Wa Siratuha Al-Kamilah Fi Shafahat. The results of this study indicate that gender equality in Islamic education according to Sheikh Buthi: First, the treatment of the Prophet Muhammad towards his wife. Second, the level of Aisyah's knowledge in this book can be seen in several fields of knowledge that Aisyah mastered. Third, Aisyah's role for women is to revive the women's assembly with her activities providing education for women. Fourth, Aisyah's sincerity is proven by the various worships she performed, including fasting for a whole year and spending most of her wealth